Effect of date of planting on development of late blight of potato in Punjab - S.S. SOKHI*, P.S. SEKHON and (Indian Phytopathology, 2002)
The effect of planting date on late blight (Phytophthora infestans) infected seed potato on late blight was studied. Blighted tubers of variety Kufri Chandramukhi (KCM) did not produce disease when planted on September 20 and 30 during 1994 and 1995under field conditions in the Punjab, India. This is attributed to inactivation of fungus due to the high soil temperature (maximum 40?oC). But blighted tubers when planted on October 20 and 30 during 1994 and 1995 produced infected sprouts and continued to produce them up to 45 days after planting. Soil temperature (maximum<30oC) was low after planting during this period and as a result the fungus remained active. Favourable conditions for disease development provided to young plants even 10 days after planting of infected tubers on September 20, during 1994 and 1995 could not induce the disease under high soil temperature conditions. Blighted tubers planted in the second fortnight of October produced maximum diseased sprouts and remained a constant source of inoculum for a long period (up to 60 days) under the environmental conditions of the Punjab.